PENGARUH KURS, SUKU BUNGA, DAN DIVIDEN PERSHARE TERHADAP HARGA SAHAM PADA SEKTOR PERBANKAN YANG TERDAFTAR DIBURSA EFEK INDONESIA TAHUN 2013– 2017 - Riziqyani, Atika; Gunistiyo, Mr.; C, Niken Wahyu (PERMANA, 2018)
The effect of exchange rate, interest rate and dividend of share price on banking sector which is listed in Indonesia Stock Exchange year 2013-2017. Essay. Tegal: Faculty of Economics and Business Universitas Pancasakti Tegal,2018. The purpose of this study is to determine the ability of investors in considering stock prices in the banking sector in 2013-2017. Hypothesis in this research is 1) exchange rate effect on stock price. 2) interest rates affect the stock price. 3) dividend pershare effect on stock price. 4) exchange rate, interest rate and dividend pershare simultaneously affect the stock price. The population used in this study is a banking company that publishes stock prices listed on the Indonesia Stock Exchange in 2013-2017. The sample in this research are 21 banking companies. With technique of sampling using purposive sampling. The data in this research is quantitative data. Sources of data in this study are secondary sources obtained from the share price of an annual banking company published in Indonesia Stock Exchange period 2013-2017. Data collection techniques using documentation techniques. Data analysis method using descriptive statistic, classical assumption test, simple linear regression analysis, multiple linear regression analysis and coefficient of determination, then obtained the result of research that the exchange rate does not have a significant effect on stock prices, the interest rate does not significantly influence the stock price, against stock price, exchange rate, interest rate and dividend pershare have significant effect to stock price.Keywords: Rate, Interest Rate, Dividend Pershare, Stock Price